Seropositivity to Leptospira interrogans in a herd of vicuñas (Vicugna vicugna) under captivity in northern Chile - Norambuena, Cecilia; Roldán, Mariana; Tuemmers, Christian; Quezada, Gerardo; Betancourt, Oriana (Austral Journal of Veterinary Sciences, 2020)
Twenty-one vicuñas (Vicugna, vicugna) from a Chilean breeding unit were tested to serovars Pomona, Canicola, Copenhageni, Ballum and Grippotyphosa of Leptospira interrogans using the microscopic microagglutination technique. The results showed that 23.8% of the samples reacted to the serovar Grippotyphosa which has been related to abortions in South American camelids.